A prospective report on histopathological study of ovarian tumor in a tertiary care center - Rahmath Unissa; Khatija Shameem; Hafsa Saleem; B. Pramida; M.Bhavani; T Jaya Chandra (Tropical Journal of Pathology and Microbiology, 2022)
Introduction: Ovarian tumors (OTs) are the most notorious gynecological lesions in the reproductive age group. With this, a study was conducted to categorize the ovarian lesions into benign, borderline and malignant lesions and also to study their laterality, gross and microscopic patterns. Settings: The study was conducted in the Department of Pathology, KIMS, Narketpally, Telangana from January 2017 to December 2019, 36 months. Random sampling was considered. Women aged >18yrs, histologically proven OTs, sized > 5 cm diameter, were included. Abdominal hysterectomy specimen were considered. Gross examination was done. The features such as size, the color of the specimen were noted. The stained sections were examined under a light microscope for histopathological diagnosis. Results: Out of 94 participants, 79 were benign tumors (Bet), 5 were borderline tumour (BoT), and 10 were malignant tumor (MIT). Among the BeT, maximum were diagnosed in 21 – 40 years group, 21 – 40 years group in BoT and 41 – 60 years for MlT. In this research, 91% were unilateral, and Seromucinouscystadenoma was the common bilateral tumor. Among the different histological patterns, surface epithelial tumours constituted the majority. Conclusion: Maximum number of tumour cases were benign, reported in the reproductive age group, whereas the malignant neoplasms in > 40 yrs. The present study emphasizes the need for proper histopathological evaluation and screening at all ages due to the relative predominance of OTs to rule out malignancies.